Dynamic Effects of Promoters on Associative Desorption - Sales, Jose Luis (2000)
The kinetics of the associative desorption of A2 in the presence of coadsorbed species B is studied under conditions of nonequilibrium using the analysis of thermal desorption spectra obtained via Monte Carlo simulation. The surface reaction is expected to be strongly influenced by the mobility of the adsorbed species B. Thus, the reaction A(s)+A(s)+B(s)→A2(g)+2s+B(s) is proposed where x indicates the adsorbed phase, and a surface site, and g denotes the gas phase. A rich variety of behaviors is found that depended on the interplay between the concentration of promoter species, the mobility of species A and B, and interparticle interactions.